Evolution of Neonatal Screening Program in a reference hospital in Ceará: 11 years of observation - Carvalho, Daniela Cavalcanti e Silva Novais; Macedo, Tereza Callou Couto; Moreno, Magnollya; Figueiredo, Francisco Winter dos Santos; Sales, Iara Bezerra; Christofolini, Juliana; Bianco, Bianca; Barbosa, Caio Parente; Christofolini, Denise Maria (ABCS Health Sciences, 2017)
Introduction: The National Neonatal Screening Program (PNTN) aims to detect pre-symptomatic congenital diseases. This test is performed across all States of Brazil with different realities concerning the incidence of diagnosed diseases due to the diverse national ethnicity observed. Accurate knowledge about diseases’ incidence allows the elaboration of public policies for prevention and treatment. Objective: To evaluate the efficacy of neonatal screening program from a reference hospital in the State of Ceará for 11 years. Methods: Cross-sectional study based on medical records of children born between 2002 and 2012 in the referred hospital. Results: Of the 5,000 exams performed, 2,893 complete medical records (57.8%) were included in the sample. Of these, two cases of phenylketonuria and three cases of hypothyroidism were observed. As almost half of the results had not been properly registered in patients’ clinical records, the calculation of diseases frequency in this population was not reliable. Conclusion: Failure to register data of the screening test may impair knowledge acquisition of municipal and hospital managers when it comes to the number of cases in each region, consequently leading to a failure in treatment strategies. It is necessary to organize a digital database and to train health professionals to fill test result forms in order to enable early diagnosis and treatment, as well as to properly delineate a credible scenario of diseases’ prevalence in Brazil.